Pullulation of toxigenic Fusarium and Deoxynivalenol in the malting of de minimis infected barley (Hordeum vulgare). (October 2019) - Yu, Junhong; Yin, Hua; Dong, Jianjun; Zhang, Cui; Zhang, Bo; Jin, Zhao; Cao, Yan
Abstract: Malting barley is the main grain ingredient of beer brewing, but the grain crop is susceptible to Fusarium worldwide. In the study, effect of malting on the development of Fusarium toxigenic tri5 DNA and Deoxynivalenol (DON) was evaluated on barleys of naturally de minimis contamination by means of quantitative PCR and LC/MS, respectively. Twenty malting barley samples were collected from Chinese market and represented a range of DON levels below 0.75 mg/kg. The DON level was prone to decrease or remain consistent in 18 malts, but it increased in 2 malts. DON levels in the 20 malt samples were all below 0.70 mg/kg, and they were 78% on average of that presented on initial ungerminated barley. Fate of Fusarium tri5 DNA and DON was tracked during the malting of 5 barley samples, in which DON levels developed diversely. It was found that the dramatic growth of steeping-remained Fusarium was responsible for DON reproduction in barley germination, with 4.8-fold increase of tri5 DNA level on average. It made sense of the correlation (R 2  = 0.753) of barley tri5 DNA contents with malt DON levels (n = 20). Results in the current study demonstrated the growth of Fusarium and DON production in the malting of barley that potentially tended to be utilized in practical beer production. Graphical abstract: Image 1 Highlights: Malt DON levels represented 79% on average of that presented on raw barleys. Most Fusariums and DON were washed away by steeping barley. Fusarium grew differentially between barleys during germination. Malt DON was reproduced in diverse trend. malt DON levels were correlated with barley Fusarium tri5 DNA levels.